The pain trajectory of juvenile idiopathic arthritis (JIA): translating from adolescent patient report to behavioural sensitivity in a juvenile animal model - Annastazia E. Learoyd; Debajit Sen; Maria Fitzgerald (BMC, 2019)
Abstract Background While pain is a common symptom in JIA patients, it remains unclear why some JIA patients develop ongoing or persistent pain. Complex clinical and social settings confound analysis of individual factors that may contribute to this pain. To address this, we first undertook a retrospective analysis of pain reports in a JIA patient cohort with the aim of identifying potential factors contributing to persistent pain. We then carried out an experimental laboratory study, using joint inflammatory pain behaviour in rodents, to validate the role of these factors in the onset of persistent pain under controlled conditions. Methods Patients: Retrospective analysis of anonymised pain visual analogue scale (VAS) scores and accompanying clinical scores from 97 JIA patients aged 13-19 (mean: 16.40 ± 1.21) collected over 50 weeks. Rats: Experimental study of pain behaviour following intra-articular microinjection of complete Freund's adjuvant (CFA) in adolescents (n = 25) and young adults (n = 43). Some animals (n = 21) had been previously exposed to joint inflammation in infancy or adolescence. Results Patients: Cluster analysis of patient pain VAS scores revealed three trajectories over 50 weeks: consistently low pain (n = 45), variable pain (n = 30) and persistently high pain (n = 22). Number of actively inflamed joints did not differ in the three groups. High pain at a single visit correlated with greater physician global assessment of disease activity, while a high pain trajectory over 50 weeks was associated with more limited joints but fewer actively inflamed joints. Rats: Rodents administered ankle joint CFA also exhibit low, medium and high joint pain sensitivities, independent of joint inflammation. Prolonged inflammatory pain behaviour was associated with high background pain sensitivity, following joint inflammation at an earlier stage in life. Conclusions Both JIA patients and rodents differ in their individual pain sensitivity independent of the concurrent joint inflammation. Using experimental animal models allows us to isolate physiological factors underlying these differences, independently of social or clinical factors. The results suggest that a history of prior arthritic activity/joint inflammation may contribute to high pain sensitivity in adolescents with JIA.